Nonuniform phase-shift-key modulation for multimedia multicast transmission in mobile wireless networks. - Pursley, M.B (IEEE Journal on selected areas in communications)
It is a common requirement in a mobile wireless communication network that a radio must be capable of simultaneously transmitting a message to two or more neighbors in the network. Some of the intended recipients may be more capable than others in the sense that their communication links from the transmitter have less interference, fading, or attenuation. Because it is desirable that a multicast or broadcast transmission be received successfully by all radios for which it is intended, the usual approach is to limit the transmission rate to that which can be demodulated by the least capable among these radios. Nonuniform nonbinary phase-shift-key (PSK) signal constellations can be designed to increase the throughput of multicast transmissions by delivering additional information to more-capable receivers along with the multicast message. This additional throughput can be employed to transmit multimedia messages (e.g., voice and data) to the more-capable receivers. In this paper, we determine the error probabilities for coherent demodulation of nonuniform PSK signals and noncoherent demodulation of nonuniform differential PSK signals. Because the PSK constellations have a constant envelope, they are better for use in mobile wireless communication networks than the constellations based on quadrature-amplitude modulation that have been proposed in previous publications